1994
DOI: 10.1002/cne.903430405
|View full text |Cite
|
Sign up to set email alerts
|

Serotoninergic innervation of nonprincipal cells in the cerebral cortex of the lizard Podarcis hispanica

Abstract: The mechanism of serotoninergic transmission in the neo- and archicortex of mammals is complex, including both synaptic and nonsynaptic components, direct actions on principal cells, and indirect effects mediated by GABAergic interneurons. Here we studied the termination pattern and synaptic organization of the serotoninergic afferents in the cerebral cortex of the lizard, Podarcis hispanica, which is considered to correspond in part to the mammalian hippocampal formation, with the aim of unraveling basic, phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The distribution of 5‐hydroxytryptamine‐immunoreactive (5‐HT‐IR) neurons and fibers were extensively investigated in the cerebellum of various mammals and nonmammalian vertebrates, such as the cat (Takeuchi et al, ), the rat (Bishop and Ho, ), the opossum (Bishop et al, ), the squirrel monkey (Cha and Lee, ), the duck (Liu et al, ), the pigeon (Challet et al, ), the bullfrog (Ueda, ), and the fish (Fang et al, ). The 5‐HT‐IR neurons and their projection fibers were also found to distribute widely in the central nervous systems of various reptiles including the Siamese crocodile (Rujirekagukwat and Huggins, ), the Nile crocodile (Rodrigues et al, ); the turtle Clemmys japonica (Ueda et al, ), the turtle Pseudemys scripta elegans (Kienhn et al, ), the turtle Chrysemys picta (Larson‐Prior et al, ), the turtle Testudo horsfieldi, and the turtle Emys orbicularis (Kenigfest et al, ); the lizard Varanus exanthematicus (Wolters et al, ), the lizard Gekko gecko (Smeets and Steinbusch, ), the lizard Psammodromus algirus and the lizard Podarcis hispanica (Guirado et al , ), the Japanese grass lizard (Ohshima et al, ), the lizard Podarcis hispanica (Martínez‐Guijarro et al, ); the viper Viper aspis (Challet et al, ). Studies in several species of reptiles have demonstrated the distribution of 5‐HT in the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of 5‐hydroxytryptamine‐immunoreactive (5‐HT‐IR) neurons and fibers were extensively investigated in the cerebellum of various mammals and nonmammalian vertebrates, such as the cat (Takeuchi et al, ), the rat (Bishop and Ho, ), the opossum (Bishop et al, ), the squirrel monkey (Cha and Lee, ), the duck (Liu et al, ), the pigeon (Challet et al, ), the bullfrog (Ueda, ), and the fish (Fang et al, ). The 5‐HT‐IR neurons and their projection fibers were also found to distribute widely in the central nervous systems of various reptiles including the Siamese crocodile (Rujirekagukwat and Huggins, ), the Nile crocodile (Rodrigues et al, ); the turtle Clemmys japonica (Ueda et al, ), the turtle Pseudemys scripta elegans (Kienhn et al, ), the turtle Chrysemys picta (Larson‐Prior et al, ), the turtle Testudo horsfieldi, and the turtle Emys orbicularis (Kenigfest et al, ); the lizard Varanus exanthematicus (Wolters et al, ), the lizard Gekko gecko (Smeets and Steinbusch, ), the lizard Psammodromus algirus and the lizard Podarcis hispanica (Guirado et al , ), the Japanese grass lizard (Ohshima et al, ), the lizard Podarcis hispanica (Martínez‐Guijarro et al, ); the viper Viper aspis (Challet et al, ). Studies in several species of reptiles have demonstrated the distribution of 5‐HT in the cerebellum.…”
Section: Introductionmentioning
confidence: 99%